Influence of Motivation and Language Learning Environment on the Successful Efl Learning - Masyhur, Masyhur; Mohd, Melor; Yunus, Yunus; Mohd Yasin, Mohd Hanafi (Proceedings of the UR International Conference on Educational Sciences, 2018)
This case study investigates the influence of motivation and language learning environment on successful English as a foreign language (EFL) learning. The research examines: (1) the nature of the motivation of successful EFL learners; and (2) how language learning environment affects theirsucess.The data were obtained from six EFL learners identified as successful learners based on their high-level English language proficiency and in their overall success of the language use. EFL motivation is conceptualized and illustrated as a dynamically changing construct that plays important roles in the EFL learning process. The design of the study involves both holistic and focused analysis. Each participantâs learning history is created through individual interviews. The research traces each participantâs learning history, including motivational changes and salient motivational sources, such as their learning environments. The results showed that sustained motivation is not always present in successful EFL learning.Thesix learnersâ successesresult from their ability to sustain their learning commitment. The research also reveals that a supportive parental family environment affects their success in the EFL learning. It is not only a feature found in the participantsâ birth families and it also presents in the new families they gained after marriage. The findings provide important knowledge to language learners, language educators, and policy-makers about the critical role of motivation and commitment in EFL, in particular, in contexts where the majority of learners fail to attain high-level of language proficiency despite many years of informal or formal language study.